2020
DOI: 10.35877/454ri.qems224
|View full text |Cite
|
Sign up to set email alerts
|

Internet Usage and Economic Growth: The Case of Mexico

Abstract: This paper finds that more internet users as a percentage of total population promote economic growth in Mexico and that the impact exhibited a nonlinear relation and was greater in the initial stage of Internet adoption. In addition, less government budget deficit as a percent of GDP, a higher real stock price, real peso appreciation, a higher real crude oil price or a lower expected inflation rate would enhance economic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…Appiah-Otoo and Song (2021) indicated that the positive impact of ICT on output in the low-and middleincome countries was greater than that in the high-income countries. Wahab et al (2020), Hsing et al (2021), and Yin and Choi (2021) selected Internet users as a proxy for ICT. Wahab et al (2020), Hsing et al (2021) reported that Internet users had a positive effect on output.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Appiah-Otoo and Song (2021) indicated that the positive impact of ICT on output in the low-and middleincome countries was greater than that in the high-income countries. Wahab et al (2020), Hsing et al (2021), and Yin and Choi (2021) selected Internet users as a proxy for ICT. Wahab et al (2020), Hsing et al (2021) reported that Internet users had a positive effect on output.…”
Section: Literature Surveymentioning
confidence: 99%
“…Wahab et al (2020), Hsing et al (2021), and Yin and Choi (2021) selected Internet users as a proxy for ICT. Wahab et al (2020), Hsing et al (2021) reported that Internet users had a positive effect on output. Yin and Choi (2021) indicated that lagged Internet users had a positive impact on output for the whole sample whereas lagged Internet users did not affect output for the East Asian countries including South Korea.…”
Section: Literature Surveymentioning
confidence: 99%
“…Well before the COVID-19 virus outbreak, Janssen & Carradini (2021) discovered that Gen Z staff have an unanticipated awareness of the negatives of digital use, the existence of different priorities and proficient perceptions, the consciousness of technological advances, and concern for the boundaries between work and home, that also alerts institutions to mitigate harmful generational taboos and promote better engagement approaches to match the latest generations. Gen Z's intentions and desire to use social media are influenced by their emotions of ease and attractiveness (Hsing et al, 2020). The practical approach to address this group, according to Ajmain (2020), is to recognize their attitude, connect with them after their "tech-language," and stay current on digital technology advances.…”
Section: Social Media Usage Moderating Rolementioning
confidence: 99%
“…During this recent worldwide pandemic, online educational activities have gained momentum and countries have started to develop their distance education learning programs. Most of these activities tend to increase productivity, increase private expenditure, reduce the cost of doing business, and increase the welfare level of people and the national output (Hsing et al, 2020).…”
Section: Introductionmentioning
confidence: 99%